(untitled) (Research, Society and Development, 2021)
Objective: To assess blood glucose levels, anthropometric measurements and quality of life in patients with type 2 diabetes mellitus (DM2) who regularly practice physical activity without a professional prescription. Methods: 35 DM2 patients were studied, 16 men, aged 60.1 ± 9.5 years, divided into two groups, namely: sufficiently active (GSA=24) and insufficiently active (GIA=11), classified by the recommendations of the American College Sports of Medicine, after applying the IPAQ physical activity level questionnaire. Anthropometric measurements, fasting blood glucose, glycated hemoglobin, postprandial blood glucose and patients’ quality of life were evaluated. Results: It was documented that 24 (68.6%) of the volunteers performed 1,078.1 ± 1,481.6 min/week and were classified as GSA and 11 (31.4%) performed 58.6 ± 41.6 min/week, being classified as GIA (p=0.0001). There was no documented difference in any of the glycemic indexes assessed between the groups. In the anthropometric evaluation, only the neck circumference was smaller in the GSA (36.8±3.7cm) than in the GIA (40.2±6.1cm), p=0.04. Finally, in the assessment of quality of life, the domain of social/vocational concern was lower in the GSA (8.3±1.8) than in the GIA (9.5±1.7), p=0.04. Conclusion: The performance of physical activity without an adequate prescription does not improve glycemic indexes, anthropometric measures and quality of life of patients with DM2. A significant percentage of patients with DM2 do not exercise regularly, even after medical advice.